Diplomatic Representation of Lithuania in Washington in the 40s–50s - Jonušauskas, Laurynas (Genocidas ir rezistencija, 2002)
After the occupation of Lithuania by the Soviets in 1940, the Lithuanian Mission in Washington became almost the most important anchor of the Lithuanian Diplomatic Service. This article reviews work of the Lithuanian Mission in Washington in the 40s-50s. At that time the Lithuanian ambassador was Povilas Žadeikis who was an active speaker for the interests of Lithuania in the USA government. He raised the questions regarding the formation of the Lithuanian exile government and "freezing" of the Lithuanian capital, which was in the US Reserve, in the bank. He was also very active within the diplomatic service, considered and made various proposals to the council members regarding forms of political authorities in exile.Due to big distance between the Lithuanian Missions in Washington and Europe, the activities of the corresponding ambassadors were not very concerted (Povilas Žadeikis was very sceptical regarding the National Committee). However, on the other hand, the role of the Lithuanian Mission and the representative himself as of a mediator between the US authorities and Lithuanian diplomats was one of the most essential in the Lithuanian Diplomatic Service.
Keywords: Soviet occupation; USA; emigree; emigree organisations; diplomacy